Ação de antibióticos macrolídeos (azitromicina e espiramicina) sobre o perfil de produção de citocinas em linhagem de células tro-foblásticas BeWo e mielomonocíticas THP-1 infectadas por Toxoplasma gondii - Franco, Priscila Silva (2011)
Toxoplasma gondii is an obligate intracellular parasite that infects a wide range of hosts and infection cases are severe in immunocompromised individuals and during pregnancy. The macrolide antibiotics have proven effects in control of toxoplasmosis. BeWo trophoblast cell lineage and myelomonocytic cell line THP-1 are used as experimental models for infection by T. gondii. Therefore, this study aimed to verify the effect of azithromycin or spiramycin in the cytokine production modulation in infected or non-infected BeWo and THP-1 cells by T. gondii. First, the cells were treated with different concentrations of azithromycin or spiramycin to cell viability analysis using the colorimetric assay of thiazolyl blue tetrazole (MTT). BeWo cells showed lower viability in concentrations greater than 400 μg/mL for both drugs, while THP-1 cells showed less viability in concentrations greater than 200 μg/mL. The treatment with drugs decreased of parasitism, as well as intracellular replication of T. gondii in BeWo and THP-1 cells. T. gondii infection induced up-regulation of the macrophage migration inhibitory factor (MIF) in BeWo cells and the production was enhanced in treated infected BeWo cell with azithromycin. Treated and infected BeWo and THP-1 cells increased anti-inflammatory cytokine IL-10, IL-4 and IL-5 production. In conclusion, the present study demonstrated that treatment of BeWo and THP-1 cells with azithromycin or spiramycin is able to control the infection and replication of T. gondii. In addition, the treatment with these drugs induce an anti-inflammatory immune response and high production of MIF that are important factors for establishment and maintenance of pregnancy.